Building bridges over troubled waters: Administrative change at the regional level in European, multilevel water management. Issue 5 (20th October 2018) - Indset, Marthe
ABSTRACT: The European Commission is promoting more decentralized forms of multilevel administration, without having its own administrative capacity on the ground. This article examines the role of ground-level administration in this multilevel system, by analysing why and how administrative change at sub-national levels comes about in connection with the implementation of European Union (EU) legislation. Despite their similar unitary state systems, Sweden and Norway have implemented the administrative requirements of the Water Framework Directive differently. While Sweden has delegated decision-making authority to novel regional-level bodies, triggering frictions in the hierarchical structure of government, Norway established networked, interdependent structures. Enquiring into the causes, the study finds that complementary use of instrumental, power-oriented and historical institutionalism shed light on the conditions under which European multilevel administration develops. In complex political-administrative systems, domestic legacies and time-specific events provide 'turfs' for Europeanization-processes shaping domestic administrative systems from within.